Peran Moderasi Pengalaman Layanan BPJS dalam Hubungan antara Kelompok Referensi dan Niat Pembelian Telemedisin - Dewi Purnama Sari; Silvi Nur Rohma; Yesica Apriliana Paska (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2026)
This study examines the influence of reference groups on telemedicine purchase intention among BPJS Kesehatan participants in Indonesia, with BPJS service experience as a moderating variable. Data from 105 respondents were analyzed using PLS-SEM via SmartPLS 4.0, with sample adequacy confirmed through G*Power analysis (power = 0.81). Results show that value-expressive influence significantly and positively affects telemedicine purchase intention, while informational and utilitarian influences show no significant direct effects. Notably, BPJS service experience significantly and negatively moderates the relationship between value-expressive influence and purchase intention, indicating that greater service dissatisfaction weakens identity-based social motivations rather than strengthening them. This finding extends the Push-Pull-Mooring framework by revealing that severe institutional dissatisfaction suppresses rather than amplifies value-expressive influence. The study highlights the contextual role of public healthcare experience in digital health adoption decisions.